Pengaruh Kemandirian Belajar terhadap Kemampuan Pemahaman Konsep Matematika Siswa SMA - Aulia Masruroh Aulia; Rita Kusumawardani (Educational Journal, 2026)
Students from various educational levels experience difficulties in learning mathematics. The first problem in learning mathematics is the difficulty in understanding mathematical concepts. Some students forget the main material that was discussed at the previous level. The second problem is students' perception of mathematics. Students view mathematics as a difficult and boring subject, which makes them lazy to study mathematics. The third problem is the lack of motivation due to online games. Students tend to be happy when playing, but are not enthusiastic when taking math lessons. Students studying mathematics must understand mathematical concepts first so they can solve problems and able to apply this learning in the real world.  The purpose of this study is to determine how much influence learning independence has on the mathematical concept understanding ability of grade 10 students of SMAN 80 North Jakarta. The method used in this study is the simple regression analysis method. The sample in this study was 55 students taken using a purposive sampling technique. Before conducting the hypothesis test, the data is tested for normality and linearity.  Data analysis using simple regression. The results of the study show that there is a positive influence between learning independence and the ability to understand mathematical concepts of 72,18% with the regression equation ????̅= 83,42 + 0,02x and thitung > ttabel = (3,246 > 2,006.